Herbegrafenis van de gevallen communistische verzetsstrijders Holstege, V.d. Logt, Van 't Veen - Naeff, Nico
Herbegrafenis van de gevallen communistische verzetsstrijders Holstege, V.d. Logt, Van 't Veen.